A sensor for fruit classification using doppler radar - Leekul, P.; Krairiksh, M. (My University, 2018)
This paper presents a microwave sensor that can detect defected fruits. In this work, mangosteen is used as an example. Translucent is detected by measuring Doppler frequency as mangosteen is rotated. From the simulated scattered waves at different directions around the fruits, the different in scattered wave results in Doppler signal from the defected fruit. The different D.C. voltage from the mixer identified whether there is translucent for the whole fruit. This cost effective sensor is a good candidate for fruit classification.
Keywords: Doppler radar; fruit classification; mangosteen; microwave sensor